Silva Kaputikyan in Connections with Russian Poets (by Her Library and Archives) - KHANJYAN, NATALYA (Bulletin of Yerevan University H: Russian Philology, 2021)
Тhe connections of outstanding Armenian poetess Silva Kaputikyan with Russian literature, in particular with poetry, its classics and contemporaries, are a topic of special interest. These connections were close and they revealed differently: literary contacts, mutual translations, creative collaboration, close friendship etc. The article gives the picture of this connections, marks out among them most important and fruitful ones. The theme is presented by the author on the basis of his acquaintance with S.Kaputikyan’s personal library and archives. Some new materials are publicated.